Behaviour of Oriza Stiva Under Variable UV Radiations (International Journal of Agriculture and Sustainable Development, 2021)
Solar UV radiation at the earth's surface grows as the ozone layer depletes, affecting economically vital plants. The effects of UV radiation on germination, growth, chlorophyll content, and fresh and dry weight of Oriza Stiva were investigated in this study. Oriza Stiva seeds were placed in plates and subjected to UV light for 30, 60, and 120 minutes each day. UV radiation lowered the percentage of seeds that germinated. Increased UV exposure significantly slowed seedling root and shoot growth. In comparison to the control, UV irradiation had a beneficial effect on chlorophyll contents, increasing total chlorophyll content. According to the findings, UV radiation reduced radicle and plumule lengths while increasing chlorophyll content in Oriza Stiva